Oleophilic bio barriers (OBBs) for control of hydrocarbon sheens at groundwater-surface water interfaces - Chalfant, Marc William, author; Sale, Tom, advisor; Butters, Greg, committee member; Gooseff, Michael, committee member (Colorado State University. Libraries, 2015)
Sheens are a common problem at petroleum facilities located adjacent to surface water bodies. Thin, iridescent films of Non-Aqueous Phase Liquid (NAPL) can form on surface water sporadically and unpredictably via three processes: seeps, ebullition, and/or shoreline erosion. Because the appearance of sheens can elicit a notice of violation of the Clean Water Act, a suite of remedies has been used to address them. Common remedies are often predicated on physical barriers and sorbent barriers, both of which can be expensive and/or prone to failure due to bypass and/or finite storage capacities. Groundwater-Surface water Interfaces (GSIs) are active biological zones where NAPL fluxes are attenuated via aerobic biological degradation. Physical and sorptive barriers can inhibit aerobic degradation processes by causing NAPL to accumulate, preventing oxygen delivery or introducing organic matter that exerts an oxygen demand. Shortcomings of current sheen remedies motivate the research presented herein, exploring the concept of aerobic reactive barriers at GSIs. Specifically, the concept of an Oleophilic Bio Barrier (OBB) is advanced. An OBB prevents sheens due to seeps, ebullition, and erosion by employing 1) an oleophilic geocomposite to sorb NAPL, 2) aerobic degradation of NAPL via naturally occurring microbes, and 3) structural cover to mitigate erosion. A full US patent detailing these concepts was submitted to the US patent office in September 2014 (Zimbron et al., 2014). The work presented herein includes laboratory studies, a preliminary field study, a full-scale field demonstration and a general estimate of construction costs. Results of the lab studies provided proof-of-concept that a geocomposite material in an OBB could prevent sheens. The geocomposite was shown to have a capacity of 3L of NAPL/m². The geocomposite was also shown to reduce dissolved hydrocarbon concentrations by up to 77%. The preliminary field study showed that an OBB could be used to prevent sheens in a field setting. Four 1m x 1m OBBs were installed in March 2013 and monitored through August 2013. In August, NAPL saturations of up to 1.6 L/m² were measured in the OBBs, demonstrating their ability to prevent sheens. The geocomposite maintained structural integrity, suggesting chemical compatibility with the NAPL. A low redox potential (62 mV) and the presence of dissolved iron (9.0 mg/L) at 90 cm depth showed that subsurface sediments were anaerobic. Redox potentials ranging from 302 to 423 mV were measured in the OBB water, demonstrating that aerobic degradation could occur and deplete NAPL on the OBBs. Results from the full-scale (36 ft x 18 ft) OBB module study demonstrated sheen prevention and microbial activity. Of 26 visual inspections for sheens, no sheens were observed sourcing from the OBB, while 3 inspections yielded sheen observations on adjacent shoreline. Seasonal changes in sorbed NAPL composition were consistent with patterns of microbial degradation and correlated to decreased redox potentials and warm temperatures. Microbial populations in the OBB were comparable to adjacent and underlying sediments but showed increased diversity of hydrocarbon-degrading microbes. In addition, structural cover was shown to mitigate erosion associated with ice-scour, while sustaining minimal damage and sedimentation. Costs for OBB construction were estimated to be on the order of $100,000 per acre, making more affordable than organoclay barriers and sheet pile barriers. The primary conclusion of this thesis is that OBBs are a viable technology from both cost and performance perspectives. Recommendations for future work include OBB design modifications for improved sediment control, greater compatibility with natural environments, and enhanced NAPL retention capacity. Simplified performance monitoring, research on governing processes, methods for characterizing sheen sources, and the development of a model to support OBB design optimization are also recommended. Ongoing consideration of expanding the full-scale OBB module and active consideration of OBB remedies at other sites provide promising opportunities for further development.
Keywords: hydrocarbons; petroleum; sheens; NAPL; environmental; remediation